2011
DOI: 10.4103/0975-7406.80768
|View full text |Cite
|
Sign up to set email alerts
|

Studies on aerial parts of Artemisia pallens wall for phenol, flavonoid and evaluation of antioxidant activity

Abstract: Herbs have been used for medicinal purposes for centuries. According to recent investigations, they may help reduce the risk of chronic diseases, cardiovascular disease, and cancer due to antioxidant properties, which in turn can be attributed to the various phytoconstituents. With this intention, evaluation of antioxidant activity was performed. Methanol extract of aerial parts of Artemisia pallens Wall was screened for its antioxidant activity due to phenolic and flavonoid contents, by employing radical scav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…Our results suggested that almost all herbal ingredients, i.e., AD, AP, LC, NJ, PK, SC, and TC, served as scavengers of specific ROS and RNS, which was further supported by previous evidence 17, 18, 19, 20, 21, 22, 23, 24. To the best of our knowledge, the scavenging properties of AP against O 2 •− and of SC against OH • have not been reported elsewhere.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results suggested that almost all herbal ingredients, i.e., AD, AP, LC, NJ, PK, SC, and TC, served as scavengers of specific ROS and RNS, which was further supported by previous evidence 17, 18, 19, 20, 21, 22, 23, 24. To the best of our knowledge, the scavenging properties of AP against O 2 •− and of SC against OH • have not been reported elsewhere.…”
Section: Discussionsupporting
confidence: 89%
“…Our results suggested that almost all herbal ingredients, i.e., AD, AP, LC, NJ, PK, SC, and TC, served as scavengers of specific ROS and RNS, which was further supported by previous evidence. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 To the best of our knowledge, the scavenging properties of AP against O 2 •− and of SC against OH • have not been reported elsewhere. It can be observed that, with the exception of TC, when individually assayed for their antioxidant activities and cytotoxicity, both the hydroethanolic and the water extract of each herbal ingredient in PN appeared to be less active than the polyherbal combination of PN.…”
Section: Discussionmentioning
confidence: 95%
“…The antioxidant potential in various medicinal plants has been shown mainly due to phenolic compounds [11][12][13][14][15][16]. Likewise, different species of the genus Artemisia including A. absinthium L. have shown phenolics associated antioxidant activities [4,[17][18][19]. Furthermore, the importance of flavonoids as antioxidants and their role in antimalarial and anticancer activities of A. annua has been reviewed [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have reported that it is used as antifungal, antiviral, and antimalarial agent. It is used to treat diabetes mellitus, rheumatoid arthritis and lupus nephritis [3]. The second plant, M. hortensis belongs to family Lamiaceae, finds its place in religious ceremonies and has several uses in therapeutic remedies, insecticidal effect due to terpenes, and carries several traditional uses [4].…”
Section: Introductionmentioning
confidence: 99%